2017
DOI: 10.1016/j.joca.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy impact of human cartilage: predictors for microcracking the network of collagen

Abstract: An impact energy density of 1.0 mJ/mm corresponded to a ∼20% probability of microcracking. Such changes may initiate a degenerative cascade leading to post-traumatic osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The observations were done in the entire 100 µm‐section and in adjacent thick sections and were always confined to the necrotic areas. Furthermore, almost identical ripples and microsplits were observed using SHG in osteoarthritic cartilage and a similar fissure or microcrack was revealed by SHG in cartilage upon low‐energy impact . The findings were therefore assumed to be valid and not artifacts from sample preparation.…”
Section: Discussionmentioning
confidence: 56%
“…The observations were done in the entire 100 µm‐section and in adjacent thick sections and were always confined to the necrotic areas. Furthermore, almost identical ripples and microsplits were observed using SHG in osteoarthritic cartilage and a similar fissure or microcrack was revealed by SHG in cartilage upon low‐energy impact . The findings were therefore assumed to be valid and not artifacts from sample preparation.…”
Section: Discussionmentioning
confidence: 56%
“…It has further been shown that tissue softening due to excessive loading can precede collagen denaturation, which seems logical since the interconnections between the collagen fibrils are weaker in tension than the fibrils themselves . Cartilage exhibits increased swelling and softening with higher loads, reveals more microcracks within the collagen network with higher impact energy or applied stress or stress rate, and levels of degraded collagen coincide with or come at a later stage than cell death indicating that this is also caused by excessive microstrains . The increased compliance within the tissue as a result of collagen network de‐structuring has the potential to affect chondrocyte metabolism and the microstructural response to compression.…”
Section: In Vitro Studies; Short‐term Resultsmentioning
confidence: 99%
“…Based on preliminary studies, we selected LI ¼ 1.5e2.5 mJ/mm 3 and HI ¼ 2.5e4.0 mJ/mm 3 . Based on our previous work, 1 we selected the intended impact velocity v à imp ¼ 0:5 m/s. We calculated the required drop height h ¼ ðv à imp Þ 2 =2g, with g as gravitational acceleration.…”
Section: Low-energy Impactmentioning
confidence: 99%
“…4,5 While microcracks in bone have been characterized extensively, 6e10 and sub-millimeter-scale surface fissures in cartilage are well known for early to advanced osteoarthritis (OA), 11e14 we recently demonstrated that low-energy impact usually considered non-injurious can in fact cause micrometer-scale cracks (microcracks) in the collagen network of human cartilage. 1 In previous work we defined collagen-network microcracks as fractures in the collagen network that are no wider than the diameter of chondrocyte lacunae ( < 30 mm). 15,16 Furthermore, we probed the diminished functional response of cartilage under progressive cyclic loading 17 and found statistically significant microcracking under some loading conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation